EPISTEMOLOGI ILMU DALAM PENDIDIKAN ISLAM: ANALISIS STUDI PUSTAKA TERHADAP DIKOTOMI, INTEGRASI, DAN INTERKONEKSI ILMU PENGETAHUAN - Pausil; Muhammad Zalnur; Armai Arief (As-Sulthan Journal of Education, 2026)
The epistemology of knowledge is a crucial foundation in the development of Islamic education because it determines the perspective on the source, validity, and purpose of knowledge. A persistent problem in contemporary Islamic education is the dichotomy between religious and general knowledge, which has resulted in fragmentation of knowledge and a weakening of the integration of Islamic values. This study aims to analyze the epistemology of knowledge in Islamic education through an examination of the concepts of dichotomy, integration, and interconnection of knowledge. This study uses a qualitative approach with library research methods, examining the works of classical and contemporary Muslim thinkers and scientific journal articles relevant to the philosophy of knowledge and Islamic education. Data analysis techniques include content analysis and conceptual-philosophical analysis to uncover the epistemological assumptions and educational implications of these concepts. The results of the study indicate that the dichotomy of knowledge is a historical construct influenced by the paradigm of Western secularism and is inconsistent with the Islamic worldview. The concept of integration of knowledge seeks to unite religious and general knowledge within the framework of monotheism, while the approach of interconnection of knowledge emphasizes dialogue and interdisciplinary connections in understanding the complexity of reality. This research confirms that the integrative-interconnective paradigm is a relevant epistemological approach to reconstruct Islamic education to make it more holistic, valuable, and responsive to the challenges of the times.